Pattern of critical congenital heart disease and their outcome in Northern India: a medical school based study - Lone, Mohd Rafiq; Qazi, Mahvish; Saqib, Najmus (International Journal of Research in Medical Sciences, 2019)
Background: Critical congenital heart disease (CCHD) comprise a group of morphologically heterogeneous disorders which have one thing in common that early surgical or catheter interventional therapy is mandatory to achieve survival. Our aim in this study was to look for pattern of Critical congenital heart disease in a tertiary centre in Northern India. Methods: Our study was a hospital based prospective study conducted on all patients with suspected congenital heart disease who were brought to neonatology section of a tertiary care hospital. The methods employed for case detection used were clinical examination, pulse oximetry, chest radiograph, electrocardiogram and echocardiography. Results: Forty two neonates with suspected congenital heart disease were admitted in our NICU (Neonatal intensive care unit) and nine cases of CCHD were diagnosed. Twenty seven cases were having Non Critical cardiac lesions whereas six cases had respiratory illness. Out of nine cases of CCHD seven patients died while two are alive. Conclusions: With the advent of more screening tools the prevalence of CCHD has increased and the mortality associated with this condition is also very high. It is thus imperative to go for early surgical correction to achieve survival.